2008
DOI: 10.1002/mus.20981
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing measurement of the electrical anisotropy of muscle

Abstract: Skeletal muscle is electrically anisotropic, with applied high-frequency electrical current flowing more easily along than across muscle fibers. As an early step in harnessing this characteristic for clinical use, we studied approaches for maximizing the measured anisotropy by varying electrode size and applied current frequency in the tibialis anterior of 10 normal subjects. The results were compared to those from two patients with amyotrophic lateral sclerosis (ALS). Current was applied percutaneously, first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 12 publications
2
42
0
Order By: Relevance
“…Frequency-dependence to the changes was observed in our one other study assessing anisotropy alterations in the tibialis anterior muscle of human subjects (Chin et al, 2008), although drawing comparisons between these two investigations is difficult since in that study only two ALS individuals were studied. Interestingly, in that study, the subject with very longstanding atrophy and weakness of the tibialis anterior (the one muscle studied) showed a flattening of the spectrum and reduction in anisotropy, whereas the one with only moderate weakness of the tibialis anterior muscle showed an elevation across the frequency spectrum, suggesting that the duration of neurogenic injury also affects the muscle’s anisotropy.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Frequency-dependence to the changes was observed in our one other study assessing anisotropy alterations in the tibialis anterior muscle of human subjects (Chin et al, 2008), although drawing comparisons between these two investigations is difficult since in that study only two ALS individuals were studied. Interestingly, in that study, the subject with very longstanding atrophy and weakness of the tibialis anterior (the one muscle studied) showed a flattening of the spectrum and reduction in anisotropy, whereas the one with only moderate weakness of the tibialis anterior muscle showed an elevation across the frequency spectrum, suggesting that the duration of neurogenic injury also affects the muscle’s anisotropy.…”
Section: Discussionmentioning
confidence: 84%
“…There is also a strong frequency-dependence to this property. In fact, this characteristic of muscle was recognized nearly 50 years ago (Rush 1962; Fatt 1964), but its potential value for muscle disease assessment has only recently been appreciated (Garmirian et al, 2009; Chin et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…perpendicular to them) (Aaron et al 1997; Tarulli et al 2006). We have also previously demonstrated that patients with a variety of neuromuscular diseases have a disrupted muscle anisotropy compared to healthy individuals (Chin et al 2008; Garmirian et al 2009). …”
Section: Introductionmentioning
confidence: 84%
“…The anisotropy of the muscle can also be assessed by using this approach since the direction of applied current flow can be varied along with the voltage electrodes, by rotating the four-electrode set around a center point over the muscle of interest (Figure 4), and thus providing a detailed assessment of the impedance characteristics of the muscle in different directions 7. The one major disadvantage to this approach is the effect of the skin-fat layer the current must traverse.…”
Section: General Approaches To Performing Impedance Measurement On Mumentioning
confidence: 99%